Random Telegraph Noise in Metal‐Oxide Memristors for True Random Number Generators: A Materials Study. (23rd April 2021) - Li, Xuehua; Zanotti, Tommaso; Wang, Tao; Zhu, Kaichen; Puglisi, Francesco Maria; Lanza, Mario
Abstract: Some memristors with metal/insulator/metal (MIM) structure have exhibited random telegraph noise (RTN) current signals, which makes them ideal to build true random number generators (TRNG) for advanced data encryption. However, there is still no clear guide on how essential manufacturing parameters like materials selection, thicknesses, deposition methods, and device lateral size can influence the quality of the RTN signal. In this paper, an exhaustive statistical analysis on the quality of the RTN signals produced by different MIM‐like memristors is reported, and straightforward guidelines for the fabrication of memristors with enhanced RTN performance are presented, which are: i) Ni and Ti electrodes show better RTN than Au electrodes, ii) the 50 μm × 50 μm devices show better RTN than the 5 μm × 5 μm ones, iii) TiO2 shows better RTN than HfO2 and Al2 O3, iv) sputtered‐oxides show better RTN than ALD‐oxides, and v) 10 nm thick oxides show better RTN than 5 nm thick oxides. The RTN signals recorded have been used as entropy sources in high‐throughput TRNG circuits, which have passed the randomness tests of the National Institute of Standards and Technology. The work can serve as a useful guide for materials scientists and electronic engineers when fabricating MIM‐like memristors for RTN applications. Abstract : Manufacturing parameters such as type of metallic electrodes, type of insulator, thickness of the insulator, deposition methods, lateral size have an important influence on the electrical properties of memristors. In this paper, the effect of each parameter on the quality and stability random telegraph noise signals driven by memristors is discussed, and the devices showing best the performance to emulate true random generators for encrypted code generation are used.